Asset prices, collateral and bank lending: The case of Covid-19 and real estate - Aoife Horan; Barbara Jarmulska; Ellen Ryan (European Central Bank (ECB), 2023)
Our paper uses credit registry data for the euro area to examine how the banking system transmits asset price shocks to credit via revaluation of collateral and subsequent lending decisions. Specifically we examine banks' treatment of real estate collateral during the Covid-19 crisis. First we find evidence of significant frictions in the transmission of asset price dynamics to collateral values. Despite this we find that lending relationships reliant on real estate collateral received one third less credit following the outbreak of the pandemic and that firms experiencing downward revaluations of their collateral were significantly less likely to be given new loans. Our findings confirm that the collateral channel does create an economically significant link between real estate values and credit but suggest that the banking system's role in transmission may be more complex than traditional economic theory would imply.
Keywords: G21; R3; C55; 330; Real estate; collateral channel; financial accelerator; banking; microdata